Fish banks: An economic model to scale marine conservation. (November 2016) - Sala, Enric; Costello, Christopher; De Bourbon Parme, Jaime; Fiorese, Marco; Heal, Geoff; Kelleher, Kieran; Moffitt, Russell; Morgan, Lance; Plunkett, Jayne; Rechberger, Kristin D.; Rosenberg, Andrew A.; Sumaila, Rashid
Abstract: Only 2.1% of the ocean is in actively managed marine protected areas (MPAs). Achieving the United Nations' target of 10% of the ocean protected by 2020 will require an aggressively implemented mix of large MPAs in remote areas, and small MPAs in inhabited coastal areas. Replication of small no-take MPAs (marine reserves) in coastal areas at the global scale is more likely to occur if reserves are designed as investment opportunities – 'fish banks' that produce new profits based on ecosystem services such as tourism and fish production. Here a pro forma business plan for a marine reserve using private investment and local management is presented. Total annual profit before the reserve was €254, 000 (from fishing only); in year 8 after creation of the reserve, profit (fishing+tourism) was €3.3 million. Given the right conditions, the net present value of the reserve can be between 4 and 12 times greater than the no-reserve counterfactual. In our model, (1) the tourism sector covers the costs of creation and operation of the reserve as an investment in a profitable business; and (2) fishers become shareholders and receive income from tourist access fees; their profits increase as soon as one year after the creation of the reserve. A series of financing mechanisms to create and manage fish banks is also proposed. If designed properly, fish banks can help restore marine biodiversity and ecosystem services, and can create jobs, help fishers, and bring in significantly greater economic profits than the absence of protection. Highlights: A business model for creation and management of marine reserves is proposed. Marine reserves can provide both economic and ecological returns. Marine reserves can be profitable and financially self-sustaining. "Fish banks" are an economic solution to scale ocean conservation.